Aging and Robotization: The Duality Between Generations and Robot Adoption - Aydin, Asli (Review of Economic Analysis, 2023)
This paper examines the bilateral relationship between the robot adoption and the age characteristics of the employment. The study analyzes the reciprocal effects of robotization on different generations and presents the analysis of the effects of age groups on the robotization of countries. Based on an instrumentalization of the System GMM estimation method of a dynamic panel dataset of 28 selected countries over 2004 and 2016, the results show that the number of young workers is affected negatively from robotization, whereas there is a positive impact of robot adoption on old workers. Evidence further suggests that robotization is triggered by the density of young workers in the workforce of the country.